Determination of the diffusion coefficient and solubility of radon in plastics - Pressyanov, D; Georgiev, S; Dimitrova, I; Mitev, K; Boshkova, T (Radiation protection dosimetry, 2011)
This paper describes a method for determination of the diffusion coefficient and the solubility of radon in plastics. The method is based on the absorption and desorption of radon in plastics. Firstly, plastic specimens are exposed for controlled time to referent (222)Rn concentrations. After exposure, the activity of the specimens is followed by HPGe gamma spectrometry. Using the mathematical algorithm described in this report and the decrease of activity as a function of time, the diffusion coefficient can be determined. In addition, if the referent (222)Rn concentration during the exposure is known, the solubility of radon can be determined. The algorithm has been experimentally applied for different plastics. The results show that this approach allows the specified quantities to be determined with a rather high accuracy-depending on the quality of the counting equipment, it can be better than 10 %.
Keywords: Humans; Algorithms; Spectrometry, Gamma; monitorování radiace; matematika; Plastics; plastické hmoty; Radiation Monitoring; rozpustnost; lidé; Mathematics; radon; spektrometrie gama; difuze; Diffusion; Czech Republic; Solubility; algoritmy; Česká republika; Radon